Methanol transformation in the presence of catalysts on the basis of carbon materials - E. V. Egorova; D. A. Bokarev (Тонкие химические технологии, 2010)
Methanol transformation in the presence of catalysts based on various carbon materials - nanofibres synthesized in the presence of Co-, Ni- and Fe-catalysts and of the carbon-carbon composite material Sibunit were studied. It was shown that the conditions of the synthesis of carbon nanofibres influence their structure and catalytical properties. A research of Cu-containing systems based on carbon nanofibers was carried out. It was found that a particle of the catalyst metal applied to the synthesis of carbon nanofibres actively participates in the interaction with methanol. Copper and cobalt promote the decomposition of methanol giving synthesis gas. Copper and ferrum show synergism in the reaction of dehydration of methyl alcohol.